2007
DOI: 10.1038/sj.onc.1210715
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cyclin D1 expression by mTORC1 signaling requires eukaryotic initiation factor 4E-binding protein 1

Abstract: There is currently substantial interest in the regulation of cell function by mammalian target of rapamycin (mTOR), especially effects linked to the rapamycin-sensitive mTOR complex 1 (mTORC1). Rapamycin induces G 1 arrest and blocks proliferation of many tumor cells, suggesting that the inhibition of mTORC1 signaling may be useful in cancer therapy. In MCF7 breast adenocarcinoma cells, rapamycin decreases levels of cyclin D1, without affecting cytoplasmic levels of its mRNA. In some cell-types, rapamycin does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
118
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(136 citation statements)
references
References 30 publications
17
118
0
1
Order By: Relevance
“…These results suggest that in this tumor model rapamycin may be having a cytostatic effect rather than a cytotoxic effect, consistent with observations in other tumor types (15). Activation of mTORC1 results in increased translation of a number of key downstream targets, including cyclin D1 and the hypoxia inducible factor 1 alpha gene (HIF-1␣) (17)(18)(19)(20). We examined the protein levels of cyclin D1 and HIF-1␣ in the stomachs and polyps of Lkb1ϩ/ϩ and Lkb1ϩ/Ϫ mice by western blot.…”
Section: Rapamycin Reduces Tumor Burden and Proliferation In Lkb1؉/؊ supporting
confidence: 64%
See 1 more Smart Citation
“…These results suggest that in this tumor model rapamycin may be having a cytostatic effect rather than a cytotoxic effect, consistent with observations in other tumor types (15). Activation of mTORC1 results in increased translation of a number of key downstream targets, including cyclin D1 and the hypoxia inducible factor 1 alpha gene (HIF-1␣) (17)(18)(19)(20). We examined the protein levels of cyclin D1 and HIF-1␣ in the stomachs and polyps of Lkb1ϩ/ϩ and Lkb1ϩ/Ϫ mice by western blot.…”
Section: Rapamycin Reduces Tumor Burden and Proliferation In Lkb1؉/؊ supporting
confidence: 64%
“…These substrates include proteins involved in the regulation of protein translation such as the p70 S6 kinase 1 (S6K1) and eukaryotic initiation factor 4E-binding protein 1 (4EBP1) (16). Among the mRNAs known to be translationally up-regulated by mTORC1 are a number of key progrowth proteins including cyclin D1, cyclin D3, Mcl-1, c-myc, and the hypoxia inducible factor 1 alpha (HIF-1␣) (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Although MEK itself was required for hyperexpression of cyclin D1, MTOR had additional but not major roles in this phenomenon. Noteworthy, it has been reported that cyclin D1 can, in turn, further activate MTOR, 69 and vice versa inhibition of MTOR can decrease cyclin D1 levels, 60,67 establishing positive feedback between them.…”
Section: Discussionmentioning
confidence: 99%
“…MTORC1 can increase cyclin D1 expression via inactivation of eukaryotic initiation factor 4E-binding protein 1. 60,61,67,68 Previously, the MTOR was the only pathway known to be involved in acquiring classic markers of a senescent phenotype, including cyclin D1 accumulation. For the first time, we added an additional pathway, the MAPK pathway that is required, for the acquisition of at least one hallmark of senescence: hyperaccumulation of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 inhibitors, in contrast, can suppress expression of HIF-1α and its target genes. [39][40][41] Although the precise mechanism of mTORC1 activation in the intestinal polyps remains to be investigated, our data exclude the involvement of the PI3K-Akt and Erk pathways, AMPK and the nutrient status. Instead, we found that expression of mTOR at the mRNA and protein levels was increased significantly in the polyps of Apc ∆716 mice.…”
Section: Perspectivesmentioning
confidence: 87%